2020
DOI: 10.3389/fonc.2020.572853
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Lung Immune Prognostic Index May Differ in Patients Treated With Immune Checkpoint Inhibitor Monotherapy or Combined With Chemotherapy for Non-small Cell Lung Cancer

Abstract: Background Lung immune prognostic index (LIPI) status was recently developed to predict responses to immune checkpoint inhibitor (ICI) treatments. However, it is unclear whether LIPI is a prognostic index for both patients treated with ICI monotherapy and patients treated with ICIs combined with chemotherapy (ICIs CC). Methods This retrospective study established the patterns of LIPI in Chinese patients with advanced non-small cell lung cancer. Lung immune prognostic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Neither of them is heterogeneous (I 2 = 0.0%, P=0.646; I 2 = 0.0%, P=0.639). However, the LIPI score may not predict therapeutic outcomes in cancer patients receiving chemo-immunotherapy ( 26 ). The sensitivity analysis also showed that no individual study influenced the pooled effects on OS and PFS ( Supplementary Figures 6 and 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of them is heterogeneous (I 2 = 0.0%, P=0.646; I 2 = 0.0%, P=0.639). However, the LIPI score may not predict therapeutic outcomes in cancer patients receiving chemo-immunotherapy ( 26 ). The sensitivity analysis also showed that no individual study influenced the pooled effects on OS and PFS ( Supplementary Figures 6 and 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the remaining 39 articles via the full-text view, 27 full-text articles were excluded due to lack of intended outcomes (OS, PFS), HR with 95% CI or repeatedly published studies. Finally, 12 studies published between 2018 and 2020 were included in this analysis (11)(12)(13)(14)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Retrieval Results and Study Characteristicsmentioning
confidence: 99%
“…LIPI is calculated based on pre-treatment derived neutrophil to lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) levels. It has been demonstrated as a prediction tool that differentiates likely prognosis of patients with NSCLC initiating ICI treatment [ 8 , 11 , 12 , 13 , 14 , 15 , 16 ]. Studies have also demonstrated that LIPI may differentiate prognosis in patients treated with ICIs in other cancer types, including breast cancer, hepatocellular carcinoma, melanoma, renal cell carcinoma, small cell lung cancer, and urothelial carcinoma [ 12 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to behaving as a prognostic biomarker, LIPI has been proposed as a method to classify patients subgroups with disparities in ICI treatment efficacy (i.e., a predictive biomarker) [ 13 ], albeit findings have been conflicting [ 8 , 14 , 15 , 21 , 22 ]. To date, there is minimal information of the prognostic performance of LIPI in patients with NSCLC initiating first-line, combination ICI approaches [ 11 , 12 ], and there is no information on treatment efficacy across LIPI defined subgroups in this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…In the original report on LIPI, they concluded that pretreatment LIPI was correlated with worse outcomes of ICI monotherapy, but not of chemotherapy [ 12 ]. Moreover, one report, which retrospectively analyzed 114 patients with advanced NSCLC, has concluded that LIPI could not be a prognostic marker of treatment response to ICIs combined with chemotherapy [ 16 ]. In contrast, the subgroup analysis of the IMPOWER150 trial analyzed 1148 participants and concluded that LIPI identified subgroups with significantly different survival following first-line Atezo combination therapy initiation for chemotherapy-naive, metastatic non-squamous NSCLC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%